Measurement errors in GDP and forward-looking monetary policy: The Swiss case - Peter Kugler; Thomas J. Jordan; Carlos Lenz; Marcel R. Savioz (Deutsche Bundesbank, 2004)
This paper analyzes forward-looking rules for Swiss monetary policy in a small structural VAR consisting of four variables. First, the paper looks at the ex ante inflation-output-growth volatility trade-off for a forward-looking policy aiming at a convex combination of a strict inflation and output growth targeting rule implied by this SVAR model. Thereby the paper introduces a new analytical method. Second, the paper considers the effect of measurement errors in GDP on this inflation-output-growth volatility trade-off. Third, the paper works at the impact of changing beliefs about the potential growth rate on the variability of output growth and inflation. Finally the effects of different targets in a forward-looking monetary policy on ex post or unconditional volatility of inflation and output growth is explored by a simulation exercise.
Keywords: E53; E52; 330; Structural VAR; forward-looking monetary policy; efficiency frontier; GDP measurement errors; Geldpolitik; Sozialprodukt; Statistischer Fehler; VAR-Modell; Schweiz